2014
DOI: 10.1159/000360303
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and Its Soluble Receptors-1 and -2 in Iris Neovascularization and Neovascular Glaucoma

Abstract: Concentrations of vascular endothelial growth factor (VEGF), soluble VEGF receptor-1 (sVEGFR-1) and soluble VEGF receptor-2 (sVEGFR-2) were measured by enzyme-linked immunosorbent assay in 27 proliferative diabetic retinopathy patients who had iris neovascularization (INV) with or without neovascular glaucoma (NVG). The 27 eyes were divided into two groups, consisting of INV without elevation of the intraocular pressure (IOP; INV group) and INV with elevated IOP (NVG group). Ten patients with an idiopathic mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In vitro studies revealed that VEGF-A may have neurodevelopmental, neurotrophic, and neuroprotective roles [14]. Soluble forms: sVEGFR-1 (sFlt1) and sVEGFR-2, act as endogenous VEGF-A inhibitors [3, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies revealed that VEGF-A may have neurodevelopmental, neurotrophic, and neuroprotective roles [14]. Soluble forms: sVEGFR-1 (sFlt1) and sVEGFR-2, act as endogenous VEGF-A inhibitors [3, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…When neovascular fibrous tissues occupy the trabecular meshwork, aqueous outflow is disturbed, and NVG develops eventually. [ 3 4 ] An elevation of intraocular pressure (IOP) due to NVG decreases the ocular perfusion leading to further retinal ischemia, and the ischemia in turn induces more neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model studies as well as clinical patient research show that VEGF levels increased in certain intraocular diseases with active intraocular neovascularization including retinopathy of prematurity, central retinal vein occlusion, branch retinal vein occlusion, proliferative diabetic retinopathy, and neovascular glaucoma [7,[20][21][22]. A previous study showed the VEGF levels in the plasma were significantly elevated both in POAG and normal tension glaucoma patients when compared to cataract patients [16].…”
Section: Discussionmentioning
confidence: 98%